Preparation method of microwave dielectric ceramic material based on photocuring 3D printing

The preparation of lanthanum zirconate ceramics through photocuring 3D printing technology solves the problem that lanthanum zirconate ceramics are prone to cracking and difficult to make complex shapes in traditional processes, and achieves the high density and excellent microwave dielectric properties of the ceramics.

CN119613113APending Publication Date: 2025-03-14GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023657.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing lanthanum zirconate ceramics are prone to cracking during sintering and are difficult to make samples of complex geometric shapes. Traditional processes limit the comprehensive development of their microwave dielectric properties.

Method used

Photocuring 3D printing technology is adopted to select raw materials such as yttrium stabilized zirconia and lanthanum oxide, combined with resin, photoinitiator and dispersant to form a photocured 3D printing slurry, and lanthanum zirconate ceramics are obtained after degreasing and sintering.

Benefits of technology

It effectively avoids the cracking problem of lanthanum zirconate ceramics during firing, can print samples of complex structures, improves the density and microwave dielectric properties of the ceramics, and has a more stable shrinkage rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613113A_ABST
    Figure CN119613113A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to a preparation method of a microwave dielectric ceramic material based on photocuring 3D printing, lanthanum oxide and yttria-stabilized zirconia are selected as main raw materials, resin, a photoinitiator and a dispersing agent are matched for grinding to form photocuring 3D printing slurry, and lanthanum zirconate ceramic is obtained after degreasing and sintering. By using the preparation method disclosed by the invention, various possible cracking conditions in the firing process of the lanthanum zirconate ceramic are effectively avoided, various complicated structures of lanthanum zirconate can be printed, various filters with traditional structures can be printed, and special-shaped filters with complicated structures can also be printed. Compared with the lanthanum zirconate ceramic prepared by the traditional solid-phase tabletting method, the lanthanum zirconate ceramic printed by the method has the characteristics of less proneness to cracking, higher density after sintering and more stable shrinking percentage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to a method for preparing a microwave dielectric ceramic material based on photocuring 3D printing. Background Art

[0002] Lanthanum zirconate is a pyrochlore structure ceramic with medium to low dielectric constants. The cation radius ratio of lanthanum zirconate is 1.47, and it has good stability. In addition, lanthanum zirconate also has good thermal stability and low thermal conductivity. As an excellent thermal insulation material, it also has good microwave dielectric properties.

[0003] In existing research, lanthanum zirconate is usually used as a high-temperature thermal insulation coating material, and there is little research on the microwave dielectric properties of lanthanum zirconate. Lanthanum zirconate ceramics fired by dry pressing are prone to uneven grain size, which is manifested as mottled color and uneven distribution on the surface of the sintered ceramics. It is very easy to crack during the sintering process, and only some samples with simple structures can be produced. Photocuring 3D printing can produce complex geometric shapes that are difficult or impossible to achieve with other traditional processes. Lanthanum zirconate ceramics can also be used to obtain complex special-shaped filters through photocuring 3D printing, which is difficult to achieve with traditional processes.

[0004] In the preparation process of most material photocuring 3D printing slurry, the mixed powder is not pre-fired. However, due to its own characteristics, lanthanum zirconate ceramics are extremely prone to cracking during the degreasing process after molding. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing microwave dielectric ceramic materials based on photocuring 3D printing, reduce the storage and transmission requirements of point cloud data, and improve the efficiency and quality of compression and reconstruction.

[0006] To achieve the above object, the present invention provides a method for preparing a microwave dielectric ceramic material based on photocuring 3D printing, comprising the following steps:

[0007] Step 1: selecting yttrium-stabilized zirconium oxide, lanthanum oxide, 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate, dioctyl phthalate, trimethylbenzoyl diphenylphosphine oxide, silane coupling agent KH570 and S18 as raw materials;

[0008] Step 2: Select raw materials and prepare mixed powder;

[0009] Step 3: Preparation of photocurable printing slurry;

[0010] Step 4: Degrease the printed sample;

[0011] Step 5: Sintering to obtain lanthanum zirconate ceramics.

[0012] Optionally, the yttrium-stabilized zirconia in step 1 comprises 94% ZrO 2 and 5.27% Y 2 O 3 , the purity of lanthanum oxide is 99.9%.

[0013] Optionally, the execution process of step 2 is as follows: 2 Zr 2 O 7 The chemical formula is as follows: lanthanum oxide and yttrium-stabilized zirconia are mixed in a certain proportion, zirconium oxide grinding balls and anhydrous ethanol are added in a ball-to-material ratio of 2:1, and the mixture is ball-milled at a speed of 400r / min for 6 hours. After drying, the mixture is sieved through a 100-mesh sieve, and the sieved powder is placed in a muffle furnace and pre-calcined at 1100°C for 2 hours. The calcined powder is added with 2wt% of silane coupling agent KH570 and anhydrous ethanol, and the mixture is ball-milled for a second time for 6 hours. After drying, the mixture is sieved through a 100-mesh sieve to obtain a mixed powder.

[0014] Optionally, the execution process of step 3 is specifically to put the lanthanum oxide / zirconium oxide mixed powder, resin, photoinitiator TPO, and dispersant into a ball mill, and rotate the ball mill at a speed of 400 r / min for 6 hours, and finally obtain the slurry required for photocuring printing;

[0015] The mixed powder accounts for 40 vol% of the slurry volume fraction; the resin and dispersant account for 60 vol% of the slurry volume fraction; the mass of the photoinitiator TPO is 1% of the mass of the resin; the mass of the dispersant is 6% of the mass of the powder;

[0016] The resin is a mixture of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate and dioctyl phthalate, with respective proportions of 28 vol %, 42 vol % and 30 vol %.

[0017] Optionally, the photoinitiator TPO used is 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and the dispersant is S18.

[0018] Optionally, when printing the sample, the prepared slurry is spread on a DLP light-curing printer for printing. The parameters of the light-curing printer are as follows: base curing time is 5s, the number of layers is 2, the base time is 2.5s, and the light intensity is 19.6wm / cm 2 .

[0019] Optionally, in step 4, a two-step degreasing method is used to degrease the lanthanum zirconate precursor. In the first step of degreasing, the lanthanum zirconate precursor is placed in a vacuum tube muffle furnace for vacuum degreasing. In the second step of degreasing, the lanthanum zirconate precursor is taken out and placed in an air muffle furnace for air degreasing.

[0020] Optionally, in step 5, sintering is carried out in an air muffle furnace and sintered at 1600°C to convert into lanthanum zirconate ceramics, wherein the temperature is increased at a rate of 3°C / min between 0-1000°C; the temperature is increased at a rate of 2°C / min between 1000-1600°C, and the temperature is kept at the highest temperature for 240 minutes.

[0021] The present invention provides a method for preparing microwave dielectric ceramic materials based on photocuring 3D printing, wherein lanthanum oxide and yttrium stabilized zirconia are selected as the main raw materials, and are ground with resin, photoinitiator and dispersant to form photocuring 3D printing slurry, and then lanthanum zirconate ceramics are obtained after degreasing and sintering. The preparation method of the present invention effectively avoids various cracking situations that may be encountered by lanthanum zirconate ceramics during the firing process, and various complex structures can be printed on lanthanum zirconate, and filters of various traditional structures can be printed, and special-shaped filters of complex structures can also be printed. Compared with lanthanum zirconate ceramics made by traditional solid phase pressing method, lanthanum zirconate ceramics printed by the method of the present invention are less prone to cracking, have higher density after sintering, and have more stable shrinkage. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 It is a schematic flow chart of the steps of a method for preparing a microwave dielectric ceramic material based on photocuring 3D printing of the present invention.

[0024] Figure 2 It is a schematic diagram of sintering cracking by dry pressing method in a specific embodiment of the present invention.

[0025] Figure 3 It is a schematic diagram of grain non-uniformity of the dry pressing method in a specific embodiment of the present invention.

[0026] Figure 4 This is a schematic diagram of a sample of the dry pressing method after the pre-sintering process in a specific embodiment of the present invention.

[0027] Figure 5 This is a schematic diagram of a lanthanum zirconate 3D printed sample in a specific embodiment of the present invention.

[0028] Figure 6 This is a schematic diagram of the second lanthanum zirconate 3D printed sample in a specific embodiment of the present invention.

[0029] Figure 7It is a schematic diagram of degreasing and cracking of a traditional 3D printed sample in a specific embodiment of the present invention.

[0030] Figure 8 It is a schematic diagram of the diameter of the 3D printed sample in a specific embodiment of the present invention.

[0031] Fig. 9 It is a schematic diagram of the diameter of the sample sintered by dry pressing method in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0033] See also Figure 1 The present invention provides a method for preparing a microwave dielectric ceramic material based on photocuring 3D printing, comprising the following steps:

[0034] S1: yttrium-stabilized zirconium oxide, lanthanum oxide, 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate, dioctyl phthalate, trimethylbenzoyl diphenylphosphine oxide, silane coupling agent KH570 and S18 are selected as raw materials;

[0035] S2: Select raw materials to prepare mixed powder;

[0036] S3: Preparation of photocurable printing slurry;

[0037] S4: Degreasing the printed sample;

[0038] S5: Sintering to obtain lanthanum zirconate ceramics.

[0039] The following is a further explanation of the steps:

[0040] Step S1 is a raw material preparation process, and the specific raw materials prepared include yttrium-stabilized zirconium oxide (94% ZrO2, 5.27% Y2O3), lanthanum oxide (99.9%), 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate, dioctyl phthalate, trimethylbenzoyl diphenylphosphine oxide (TPO), silane coupling agent KH570 and S18.

[0041] Step 2 is the mixed powder preparation process, according to La 2 Zr 2 O 7The chemical formula of (lanthanum zirconate) is as follows: lanthanum oxide and yttrium-stabilized zirconium oxide are mixed in a certain proportion, zirconium oxide grinding balls and anhydrous ethanol are added in a ball-to-material ratio of 2:1, and the mixture is ball-milled at a speed of 400r / min for 6 hours. After drying, the mixture is sieved through a 100-mesh sieve, and the sieved powder is placed in a muffle furnace and pre-calcined at 1100°C for 2 hours. The calcined powder is added with 2wt% of a silane coupling agent KH570 and anhydrous ethanol, and the mixture is ball-milled for a second time for 6 hours. After drying, the mixture is sieved through a 100-mesh sieve to obtain a mixed powder.

[0042] The execution process of step 3 is specifically to put the lanthanum oxide / zirconium oxide mixed powder, resin, photoinitiator TPO, and dispersant into a ball mill, and rotate the ball mill at a speed of 400 r / min for 6 hours, and finally obtain the slurry required for photocuring printing;

[0043] The mixed powder accounts for 40 vol% of the slurry volume fraction; the resin accounts for 60 vol% of the slurry volume fraction; the mass of the photoinitiator TPO is 1% of the mass of the resin; the mass of the dispersant is 6% of the mass of the powder;

[0044] The resin is a mixture of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate and dioctyl phthalate, with respective proportions of 28 vol %, 42 vol % and 30 vol %.

[0045] The photoinitiator TPO used is 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and the dispersant is S18.

[0046] When printing the sample, the prepared slurry was spread on the DLP light-curing printer for printing. The parameters of the light-curing printer were as follows: the base curing time was 5s, the number of layers was 2, the base time was 2.5s, and the light intensity was 19.6wm / cm 2 .

[0047] Step S4 is the degreasing process of the printed sample. 4. Degreasing the lanthanum zirconate precursor using a two-step degreasing method. The first step of degreasing: Place the lanthanum zirconate precursor in a vacuum tube muffle furnace for vacuum degreasing, plug the two ends of the muffle furnace with plugs, connect one end to the vacuum pump, and plug the other end with an air plug. After the above operations, enter the program into the muffle furnace, and start the muffle furnace for the first step of degreasing.

[0048] After the first step of degreasing, turn off the vacuum fan and open the air plug. Take out the lanthanum zirconate precursor and put it into the air muffle furnace for air degreasing, and set the degreasing program to run.

[0049] Step S5 is the sintering process. After the above two-step degreasing method, the lanthanum zirconate precursor has been degreased. Next, it is sintered in an air muffle furnace. Sintering at 1600°C can convert it into lanthanum zirconate ceramics. The temperature is increased at a rate of 3°C / min from 0 to 1000°C; the temperature is increased at a rate of 2°C / min between 1000 and 1600°C, and the temperature is kept at the highest temperature for 240 minutes.

[0050] Further, the present invention is compared with a lanthanum zirconate ceramic fired by dry pressing in combination with a specific embodiment, see Figures 2 to 9 :

[0051] Lanthanum zirconate ceramics fired by dry pressing are prone to uneven grain size, which is manifested as mottled and unevenly distributed color on the surface of the sintered ceramics, and are very prone to cracking during the sintering process (such as Figure 2 , Figure 3 The light-curing 3D printing in the present invention can produce complex geometric shapes that are difficult or impossible to achieve with other traditional processes. Lanthanum zirconate ceramics can also be used to obtain complex shaped filters through light-curing 3D printing, which is difficult to achieve with traditional processes.

[0052] In the process of preparing the slurry for photocuring 3D printing of most materials, the mixed powder is not pre-fired. However, due to its own characteristics, lanthanum zirconate ceramics are extremely prone to cracking during the degreasing process after molding (such as Figure 7 As shown in Figure 2, in order to solve this problem, the zirconium oxide and lanthanum oxide powders were mixed and pre-sintered at 1100°C and then ball-milled. The samples printed after pre-sintering did not crack during the degreasing and sintering process (as shown in Figure 2). Figure 5 , Figure 6 As shown). After pre-burning, the viscosity of the prepared slurry increased. In order to solve this problem, 6wt% of dispersant S18 was added during the preparation of the slurry, which reduced the viscosity of the printed slurry and met the conditions for photocuring printing. At the same time, the secondary ball milling process after pre-burning also has an effect on the dry pressing method, alleviating the cracking of the sample and the uneven grain size. However, the dry pressing method still has slight cracking (such as Figure 4 shown).

[0053] In summary, the present invention has the following technical effects:

[0054] The present invention effectively avoids various cracking situations that may be encountered in the firing process of lanthanum zirconate ceramics, and can also print various complex structures on lanthanum zirconate, and can print filters of various traditional structures, and can also print special-shaped filters of complex structures. In addition, due to its excellent thermal insulation performance, it can also print complex porous structures and be used as a carrier of high-temperature catalysts.

[0055] Compared with lanthanum zirconate ceramics produced by traditional solid phase pressing method, lanthanum zirconate ceramics produced by photocuring 3D printing are less prone to cracking and have higher density after sintering. The density of lanthanum zirconate ceramics produced by dry pressing molding is about 95%, while the density of lanthanum zirconate ceramics obtained by the above preparation method reaches more than 98%. For the same material, higher density will make the microwave dielectric properties of the material better and have a higher Q×f value.

[0056] The shrinkage rate of lanthanum zirconate ceramic samples prepared by 3D printing is also more stable. The lanthanum zirconate ceramics made by dry pressing will shrink unevenly after sintering, resulting in a slight change in the diameter and height ratio of the cylindrical samples. The lanthanum zirconate ceramics prepared by light-curing 3D printing shrink uniformly in all directions after sintering, and the diameter and height ratio of the cylindrical samples can still be accurately guaranteed after sintering. Figure 8 and Fig. 9 This is a comparison of the diameters of dry pressing and 3D printed samples after sintering. It can be seen that when the size of the green embryo is consistent, the size of the sample sintered after 3D printing is closer. By calculating the shrinkage rate, ceramic samples with higher dimensional accuracy can be prepared.

[0057] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing microwave dielectric ceramic materials based on photocuring 3D printing, characterized in that: The following steps are involved: Step 1: selecting yttrium-stabilized zirconium oxide, lanthanum oxide, 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate, dioctyl phthalate, trimethylbenzoyl diphenylphosphine oxide, silane coupling agent KH570 and S18 as raw materials; Step 2: Select raw materials and prepare mixed powder; Step 3: Preparation of photocurable printing slurry; Step 4: Degrease the printed sample; Step 5: Sintering to obtain lanthanum zirconate ceramics.

2. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 1, characterized in that: The yttrium-stabilized zirconia in step 1 includes 94% ZrO2 and 5.27% Y2O3, and the purity of lanthanum oxide is 99.9%.

3. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 2, characterized in that: The execution process of step 2 is specifically as follows: according to the chemical formula of La2Zr2O7, lanthanum oxide and yttrium-stabilized zirconium oxide are mixed in a certain proportion, zirconium oxide grinding balls and anhydrous ethanol are added at a ball-to-material ratio of 2:1, ball milling is performed at a speed of 400r / min for 6 hours, and after drying, the powder is sieved through a 100-mesh sieve. The sieved powder is placed in a muffle furnace and pre-calcined at 1100°C for 2 hours. The calcined powder is added with 2wt% of silane coupling agent KH570 and anhydrous ethanol for secondary ball milling for 6 hours, and after drying, the powder is sieved through a 100-mesh sieve to obtain a mixed powder.

4. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 3, characterized in that: The execution process of step 3 is specifically to put the lanthanum oxide / zirconium oxide mixed powder, resin, photoinitiator TPO, and dispersant into a ball mill, and rotate the ball mill at a speed of 400 r / min for 6 hours, and finally obtain the slurry required for photocuring printing; The mixed powder accounts for 40 vol% of the slurry volume fraction; the resin and dispersant account for 60 vol% of the slurry volume fraction; the mass of the photoinitiator TPO is 1% of the mass of the resin; the mass of the dispersant is 6% of the mass of the powder; The resin is a mixture of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate ethoxylate and dioctyl phthalate, with respective proportions of 28 vol %, 42 vol % and 30 vol %.

5. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 4, characterized in that: The photoinitiator TPO used is 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and the dispersant is S18.

6. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 5, characterized in that: When printing the sample, the prepared slurry was spread on the DLP light-curing printer for printing. The parameters of the light-curing printer were as follows: the base curing time was 5s, the number of layers was 2, the base time was 2.5s, and the light intensity was 19.6wm / cm 2 .

7. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 6, characterized in that: In step 4, the lanthanum zirconate precursor is degreased by a two-step degreasing method. In the first step of degreasing, the lanthanum zirconate precursor is placed in a vacuum tube muffle furnace for vacuum degreasing. In the second step of degreasing, the lanthanum zirconate precursor is taken out and placed in an air muffle furnace for air degreasing.

8. The method for preparing microwave dielectric ceramic materials based on photocuring 3D printing according to claim 7, characterized in that: In step 5, sintering is carried out in an air muffle furnace and sintered at 1600° C. to convert into lanthanum zirconate ceramics, wherein the temperature is increased at a rate of 3° C. / min between 0-1000° C.; the temperature is increased at a rate of 2° C. / min between 1000-1600° C. and kept at the highest temperature for 240 minutes.